Nurturing Compassion Development Among College Students: A Longitudinal Study. Issue 3 (2nd July 2016) - Plante, Thomas; Halman, Katherine
Abstract: Little research exists on the development of compassion among college undergraduates. This study tracks changes in compassion and identifies factors associated with these changes over the course of undergraduate students' college careers, from the time of admittance to the time of graduation. Compassion levels assessed at the point of college entrance accounted for 25% of the variance in compassion at the time of graduation. These findings provided evidence for the notion that compassion can continue to be cultivated once in college. Predictors such as diversity training, the frequency of religious service attendance, participation in community-based service-learning, political identification, and feeling valued as a member of the university community accounted for an additional 10% of the variance in compassion scores at the time of graduation. Results suggest that compassion development in college students may increase through the use of particular intentional educational experiences.